Studi Kasus Pendidikan Nilai Di Sekolah Dasar Islam Terpadu Al-Amanah, Kecamatan Lembang Kabupaten Bandung Barat - Nuryana, Ina (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2016)
Values education is a process to establish the social values of the learners. It aims to direct and guide the learners to comprehend, perceive, and internalize the values that are implemented in society so that they can behave based on those values. This research was intended to discover and explore: (1) the values that were taught by the teachers during the implementation of values education in Al-Amanah Integrated Islamic Elementary School, (2) the approach used in values education in Al-Amanah Integrated Islamic Elementary School, (3) the culture which was developed in Al-Amanah Integrated Islamic Elementary School, (4) the constraints faced by the teachers of Al-Amanah Integrated Islamic Elementary School, (5) the efforts of the teachers to overcome the obstacles, and (6) the values education’s study results in Al-Amanah Integrated Islamic Elementary School. This research used an explorative qualitative approach to explore the data source comprehensively. The type of research used was a case study, focusing on the values of education at Al-Amanah Integrated Islamic Elementary School. The source of data included the principal, teachers, learners, and parents. The research’s results show that: (1) Al-Amanah Integrated Islamic Elementary School teaches religious and moral value such as devotion, patience, sincerity, honesty, discipline, diligence, obedience, exemplary, and affection, (2) the approaches used in AlAmanah Integrated Islamic Elementary School include the use of role model, habituation, and reinforcement (reward and punishment), (3) Al-Amanah Integrated Islamic Elementary School develops Islamic and democratic culture, (4) the constrains faced by the teachers are: the difference between the environment’s condition with the education objectives of the school, teachers’ limited knowledge in values education, the lack of parents’ supervision, the influence from outside, and the differences in vision and mission with the parents, (5) the teachers’ effort to overcome the problems are: creating liaison book between teachers and parents, making consultation schedule for the parents with the teachers or school, developing good communication and cooperation with various parties, especially parents, as well as involving the parents in decision-making, and (6) there is a positive change of behavior and attitude of the learners after studying in SD IT Al-Amanah. Keywords: education, values, values education